Pengaruh Electronic Word of Mouth dan Daya Tarik terhadap Keputusan Berkunjung Wisatawan di Pinus Pengger Kabupaten Bantul - Yuliyani, Yuliyani; Suharto, Suharto (Sekolah Tinggi Pariwisata AMPTA, 2021)
This research attempts to learn the influence of electronic word of mouth and location towards tourist decisions to visit at the Pinus Pengger. The population in this research is the tourists who visited Pinus Pengger. The sample taken was 100 respondents. The method for the sampling is an accidental sampling. Data collection technique was questionnaire. The analysis of data used multiple regression analysis techniques. The results of this study indicate that together, electronic word of mouth, and attractiveness affect the decision to visit tourists in Pinus Pengger. Partially, electronic word of mouth affects the decision to visit tourists, while attractiveness does not affect the decision to visit tourists.